Metallogenic mechanism of the Houge’zhuang gold deposit, Jiaodong, China: Evidence from fluid inclusion, in situ trace element, and sulfur isotope compositions - Chi, Naijie; Han, Zuozhen; Liu, Chuan’e; Zhang, Wei; Zhang, Yanhui; Shan, Wei; Li, Zengsheng; Li, Min; Wang, Xiufeng; Sun, Yuqin (Frontiers in Earth Science, 2022)
The Houge’zhuang gold deposit is located in the Penglai-Qixia gold belt of the Jiaodong peninsula, which is a representative auriferous quartz vein-style deposit. Pyrite is the most common and main gold-bearing mineral, showing complex textures in the Houge’zhuang gold deposit. Study of the ore-related pyrite is of great significance for understanding the metallogenesis, especially of gold precipitation mechanism. In this study, Systematic microscopic observation, Fluid inclusions, electron microprobe, in situ LA-ICP-MS trace-element, and in situ sulfur isotope analyses were carried out. Three types of fluid inclusions were recognized, and the ore-forming fluids exhibited medium–low salinity and temperature, and the compositions of the fluid inclusions were mainly H2O and CO2. Three types of pyrites were identified: Py0, characterized by low concentration of As, Au, and low δ34S values (5.51 to 6.86‰). Py1, hosted in the gold-quartz-pyrite veins, and homogeneous in chemical composition with no obvious zonal growth but with notably more gold and chalcopyrite inclusions. They contain medium and uniform concentrations of As and Au-rich, and have δ34S values ranging from 7.13–7.89‰ (mean 7.44‰). Py2, arsenic-bearing pyrite and hosted in the quartz-polymetallic sulfides veins, with distinct As enrichments and As rich rims of pyrite and growth zoning. Consequently, the primary ore-forming fluids may pass through some arsenic and δ34S rich sedimentary rocks, such as Jingshan, Fenzishan, and Penglai groups. With the occurrence of stable water–rock interaction, the fluids extracted and enriched As and δ34S. Further, Au was closely associate with As, visible gold grains tended to occur in association with the Py1 at stage II, and invisible gold was related to the Au-As-rich Py2 of stage III. The As-bearing pyrites share a close spatiotemporal relationship with gold, playing an important role in the formation and exploration of high-grade gold deposits.